A band‐stop filter based on spoof surface plasmon polaritons using complementary split‐ring resonators. Issue 7 (11th April 2022) - Homayoon, Fatemeh; Heidari, Abbas‐Ali
Abstract: In this paper, a controllable band‐stop filter based on spoof surface plasmon polaritons (SSPPs) is presented using complementary split‐ring resonators (CSRRs) for ultra‐wideband (UWB) applications. Four CSRRs are inserted on the ground plane to achieve the required band rejection characteristics. The filter cutoff frequency is controlled by changing the depth of the SSPP grooves. Frequency and bandwidth of the stopband are controlled by adjusting the geometric parameters and position of the CSRRs, respectively. The Control process of the stopband is independent of the filter cutoff frequency, so adjusting the stopband does not change the cutoff frequency. Two prototypes of the proposed filter with different CSRR diameters are fabricated. The measured 20 dB rejection bandwidth for the prototypes with the CSRR diameters of 3.2 and 4 mm are 10.5–11.2 and 7.8–8.6 GHz, respectively. Measured cutoff frequency is about 13.1 GHz for both fabricated filters, which indicates that stopband control does not change the cutoff frequency. Simulation and measurement results show excellent rejection performance, so the proposed filter can be used for UWB applications.